Cameras in the classroom : educating the post-TV generation - Schoonmaker, Michael (Rowman & Littlefield Education, 2007)
"Today's students are growing up in a highly visualized world. Television, video games, and DVDs offer powerful visual images to attract the attention of children and young adults. Unfortunately for educators, technology in the classroom has yet to catch up. Is it possible to use this exciting visual technology, which is so familiar to students, to benefit learning and education? Cameras in the Classroom brings those possibilities to life. Filled with sound research and helpful tips, this book explains why there's such a need for visual learning and why an estimated one million teachers will be using video production over the next few years."--BOOK JACKET.